Penggunaan Kuesioner Oral Health Impact Profile (OHIP) Pada Penelitian Tentang Gangguan Temporomandibula (Tinjauan Pustaka) - Carolina Marpaung; Ariel Jason (Jurnal Kedokteran Gigi Terpadu, 2023)
Patient’s quality of life has been assessed for both pre-and post treatment of Temporomandibular Disorders. Oral Health Impact Profile (OHIP) is known for its validity in assesing oral health related quality of life. Its original form consists of 49 items which can be categorized into seven sub-domains. The need of having a more compact questionnaire has driven researchers to create shorter forms of OHIP49, which resulted OHIP-14 and OHIP-5. Clinical studies have been carried out to assess the psychometric value for the shorter form. However, its utilization for screening purposes needs to be evaluated in future studies.